2021
DOI: 10.3389/fspor.2021.625677
|View full text |Cite
|
Sign up to set email alerts
|

Innovation for Positive Sustainable Legacy From Mega Sports Events: Virtual Reality as a Tool for Social Inclusion Legacy for Paris 2024 Paralympic Games

Abstract: There is significant interest in how sports events and their associated legacies could act as a platform to address global challenges and engender social change. The United Nations (UN) has acknowledged the important role that sport plays in supporting the UN 2030 Agenda for Sustainable Development and the Olympic movement could be argued as central to that objective. Yet critical questions and concerns have been raised about the growing expenditure, viability, long term legacy, and impacts of mega sports even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 126 publications
(166 reference statements)
1
9
0
Order By: Relevance
“…While there will be no one-size-fits all solution to future global challenges such as delivering inclusion, we believe that when major programs are planning, the first vital step is to listen to the community most affected and to co-construct a joint mission which everyone-no matter their role in the partnership-can support and find a way to be engaged in. In common with the work in [65], we find that the right cross-sector partnership can shape the use of resources, opportunities, and influence leadership and incentives, and our research also supports their findings that engagement, motivation and joint capacity were core factors. We think each of the subsequent steps of the model will be needed to some extent or another in all cases, and we look forward to reading future work which might be better able to assign weightings between the steps for a project or sector.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While there will be no one-size-fits all solution to future global challenges such as delivering inclusion, we believe that when major programs are planning, the first vital step is to listen to the community most affected and to co-construct a joint mission which everyone-no matter their role in the partnership-can support and find a way to be engaged in. In common with the work in [65], we find that the right cross-sector partnership can shape the use of resources, opportunities, and influence leadership and incentives, and our research also supports their findings that engagement, motivation and joint capacity were core factors. We think each of the subsequent steps of the model will be needed to some extent or another in all cases, and we look forward to reading future work which might be better able to assign weightings between the steps for a project or sector.…”
Section: Discussionsupporting
confidence: 84%
“…Mass sporting events such as the Paralympic Games of London 2012 remain of considerable interest to the global community in how they can be leveraged to address social change and contribute towards the realisation of the UN Sustainable Development Goals [65]. As the authors of [66] found, these events have increasingly become part of the strategic agenda to forge positive social legacies for marginalised people, and partnerships for leveraging this social impact are becoming a critical component of large scale events [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, there has been increased criticism of the negative potential from hosting a mega-event. Critical questions and concerns have been expressed concerning the expanding expense, feasibility, long-term legacy, and repercussions of SMEs (Byers et al, 2021 ). Preuss ( 2019 ) explained that the costs of hosting and debate over a host government's expenditure of public funds, has made corruption a real possibility.…”
Section: Sport Events and Their Legaciesmentioning
confidence: 99%
“…Grix et al ( 2017 ) added to this list: urban regeneration, national pride/ feel-good factor, increased involvement and participation in physical activity, international reputation and 'soft power'. Increasingly, attention is being paid to the possibility that sporting events and their legacies could serve as a platform to address global concerns and effect social change (Byers et al, 2021 ). For example, the United Nations (UN) has highlighted the significant role that sport plays in promoting the UN 2030 Agenda for Sustainable Development.…”
Section: Sport Events and Their Legaciesmentioning
confidence: 99%